STRUCTURAL DESIGN OF PALM OIL FACTORY WAREHOUSE IN CENTRAL KALIMANTAN - Qonitah, Hanan
The Palm Oil Factory in Central Kalimantan in this final project consists of 2 main buildings, i.e. the factory building and the warehouse building. The design in this final project will only review the upper structure of the palm oil factory warehouse. The main structure of this palm oil factory warehouse is the ordinary moment resisting steel frame. This final project aims to design the steel structure of the palm oil factory warehouse, to model and to calculate the upper structure design of the palm oil factory warehouse. Finally, verification of the results of the SAP2000 software program design calculations and manual calculations is carried out. The structure is designed to be able to carry minimum loads that refer to the Indonesian National Standard (SNI) 1727:2013 concerning Minimum Loads for Designing Buildings and Other Structures, Indonesian Building Construction Standards (SKBI) – 1.3.53.1987 concerning Guidelines for Loading Planning for Houses and Buildings for wind loads, and the Indonesian National Standard (SNI) 1726:2019 concerning Procedures for Planning Earthquake Resistance for Building Structures and Non-Buildings for earthquake loads. Structural modelling and analysis assisted by SAP2000 software. Structural analysis includes checking the strength and serviceability of each structural element. The manual calculation of the crosssectional capacity of steel structural elements is carried out with reference to the Indonesian National Standard (SNI) 1729:2015 concerning Specifications for Structural Steel Buildings. Results also show that calculation of the SAP2000 agree well with the manual check.